2016
DOI: 10.1371/journal.pone.0153047
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of McMonnies Questionnaire as a Screening Tool for Chinese Ophthalmic Outpatients

Abstract: ObjectiveTo evaluate the accuracy of the McMonnies questionnaire (MQ) as a screening tool for dry eye (DE) among Chinese ophthalmic outpatients.MethodsWe recruited 27718 cases from 94 hospitals (research centers), randomly selected from 45 cities in 23 provinces from July to November in 2013. Only symptomatic outpatients were included and they were in a high risk of DE. Outpatients meeting the criteria filled out questionnaires and then underwent clinical examinations by qualified medical practitioners. We mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…It has a moderate positive and negative correlation with the OSDI (Spearman correlation coefficient, r = 0.68-0.78, p < 0.001) and TFBUT (Spearman correlation coefficient, r = −0.23-−0.56, p < 0.0001), respectively [78]. Rasch analysis has shown that the OCI-C is comparable to the OCI as a diagnostic tool [ [72,81]. This questionnaire has been validated in Chinese, with its McMonnies Index cutoff value being 15 points [37].…”
Section: Questionnaires With No Questions On Hrql Yet Good Psychometmentioning
confidence: 99%
“…It has a moderate positive and negative correlation with the OSDI (Spearman correlation coefficient, r = 0.68-0.78, p < 0.001) and TFBUT (Spearman correlation coefficient, r = −0.23-−0.56, p < 0.0001), respectively [78]. Rasch analysis has shown that the OCI-C is comparable to the OCI as a diagnostic tool [ [72,81]. This questionnaire has been validated in Chinese, with its McMonnies Index cutoff value being 15 points [37].…”
Section: Questionnaires With No Questions On Hrql Yet Good Psychometmentioning
confidence: 99%
“…CLIDE symptoms have typically been assessed using questionnaire instruments developed for DE and not specifically designed or validated for contact lens wear. These include the Ocular Surface Disease Index (OSDI) [ 15 , 16 ], the Dry Eye Questionnaire (DEQ) [ 13 ], the Standard Patient Evaluation of Eye Dryness (SPEED) [ 17 ], the Impact of Dry Eye on Everyday Life (IDEEL) questionnaire [ 18 ], the Subjective Evaluation of Symptoms of Dryness (SESoD) [ 19 ], and McMonnies’ Dry Eye Index (DEI) [ 20 – 22 ], The OSDI has been extensively validated for DE patients, and although not designed or specifically validated for CLIDE [ 4 ], has been widely used in its study. McMonnies DEI also was designed and validated for DE patients, but was later validated in a study of 70 contact lens wearers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Expected McMonnies scores are 11.7±6.0 for <25 year olds and 17.6±6.0 for >45 year olds. 13 OSDI scores of <12 indicates a normal result. 14…”
Section: Questionnairesmentioning
confidence: 99%